Precise osteotomies for mandibular distraction in infants with Robin sequence using virtual surgical planning. Issue 1 (January 2018) - Resnick, C.M.
Abstract: Mandibular distraction osteogenesis (MDO) has become the first-line operation in many centers for the management of obstructive sleep apnea (OSA) in infants with (Pierre) Robin sequence (RS) not relieved by non-surgical approaches. Preoperative virtual surgical planning (VSP) may improve precision and decrease complications for this operation. This article reports a retrospective study of RS infants who underwent MDO for OSA using preoperative VSP and three-dimensionally printed cutting guides performed by one surgeon. Seventeen subjects who had MDO at a mean age of 87 ± 96 days were included. Maxillofacial computed tomography scans were obtained 15 ± 7 days prior to MDO. Osteotomy designs included linear ( n  = 4, 23.5%), inverted-L ( n  = 11, 64.7%), and multi-angular ( n  = 2, 11.8%). Cutting guides were used successfully and osteotomies were created as planned in all cases. Devices were removed 67 ± 15.6 days after placement. Bone formation in the distraction gap was seen in all cases at device removal. All patients had successful airway outcomes. There were no major and four minor complications during the follow-up period of 458 ± 267 days. In conclusion, MDO is a successful procedure for the management of OSA associated with RS in infants, and VSP facilitates its precise design and execution.